Tecendo teias: um olhar sobre avaliação e articulação na Escola Municipal Francisco Martins Nolêto - Aquino, Elisângela Glória de (Universidade Federal do Tocantins, 2021)
This research consisted of the Course Completion Work (TCC), graduation of the Full Degree in Pedagogy - Teaching in Early Childhood Education and Initial Years of Elementary Education of the Federal University of Tocantins-UFT, Campus of Miracema do TocantinsTO , and had as objective to reflect on the evaluation process in the classes of the 5th year of the Francisco Martins Nolêto Municipal School in Miracema do Tocantins -TO. The discussions were based on the analysis of the School-Field Political Project (PPP / 2018) and official documents that guide evaluation in basic education. The theoretical framework contributed to authors who discuss the evaluation process in basic education and teacher training for the initial years of elementary school: Veiga (2002); Freire (2002); Luckesi (1998); Hadji (2001); Lime; Costa & Silva (2017); Arroyo (2001); Vasconcelos (2000); Paro (2007); Gatti (2003); Cunha (2000); Pinho (2007); Chauí (2003); Nóvoa (1992); Tardif (2002); Suanno (2015); Santos (2005); Abreu & Maseto (1990); Régnier (2002). The methodology covered in the bibliographical and descriptive research and the approach of the information was sought the approach of the qualitative research, with focus in the philosophical chain of the phenomenology. The research was based on the documentary analysis of the school-field (PPP / 2018), whose data were collected in the period from 01/04 to 06/06 of 2018. The analyzes indicate that the school-field follows an educational model directed by the municipal secretariat of education, including in reference to educational evaluation. The results indicate that the research becomes relevant for discussing the evaluation of learning as fundamental for the development not only of the students, but also of the school and the municipal network of teaching of Miracema do Tocantins-TO. On the other hand, the research shows results that can be analyzed and discussed by the school staff, aiming to verify what happened from positive and negative notes. In this way, we understand that the evaluation process is fundamental in the 5th grade classes of the field school, because the students in the following year, besides migrating to other schools, will also move on to the second phase of elementary education, which requires more in the development of skills and competences, specifically involving the summative evaluation process.